Isolation and identification of long non-coding RNAs in exosomes derived from the serum of colorectal carcinoma patients - Ng, Chin Tat; Azwar, Shamin; Yip, Wai Kien; Zahari Sham, Siti Yazmin; Jabar, Mohd Faisal; Sahak, Norren Haneezah; Mohtarrudin, Norhafizah; Seow, Heng Fong (MDPI AG, 2021)
Long non-coding RNAs (lncRNAs) are non-coding RNAs consisting of more than 200 nucleotides in length. LncRNAs present in exosomes may play a critical role in the cellular processes involved in cancer pathogenesis and progression including proliferation, invasion, and migration of tumor cells. This paper aims to identify the differential expression of exosomal lncRNAs derived from the sera of non-cancer individuals and patients diagnosed with colorectal carcinoma. These differentially-expressed exosomal serum lncRNAs may provide an insight into the pathogenesis and progression of colorectal cancer (CRC). Serum exosomes and exosomes from SW480-7 cell culture supernatants were isolated and viewed by transmission electron microscope (TEM). The particle size distribution and protein markers of exosomes derived from SW480-7 were further analyzed using the Zetasizer Nano S instrument and western blotting technique. TEM showed that exosomes derived from serum and SW480-7 cells were round vesicles with sizes ranging from 50–200 nm. The exosomes derived from SW480-7 had an average diameter of 274.6 nm and contained the exosomal protein, ALIX/PDCD6IP. In our clinical studies, six lncRNAs, namely GAS5, H19, LINC00152, SNHG16, RMRP, and ZFAS1 were detected in the exosomes from sera of 18 CRC patients. Among these six lncRNAs, the expression level of LINC00152 was found to be significantly lower in CRC patients as compared to non-cancer individuals (p = 0.04) while lncRNA H19 was significantly up-regulated in advanced-stages (stage III and IV) of CRC (p = 0.04) as compared to early-stages (stage I and II). In conclusion, the detection of lower LINC00152 in exosomes of sera from CRC patients versus non-cancer individuals and H19 upregulation in advanced stages suggests that they may play important roles in pathogenesis and progression of CRC.